Views and behaviour of young people related to protection of environment based on the example of a selected group of students – own study - Miszczak, Marta (Poglądy i zachowania młodzieży związane z ochroną środowiska na przykładzie wybranej grupy studentów − badania własne, 2019)
According to numerous studies conducted over many years, Poles’ environmental awareness is at a low level. The author substantiates the claim with a discussion of studies conducted between the 1990s and 2018 using reference materials (study reports) and literature related to environmental conservation. This part of the paper is the background on which the author presents the partial results of research conducted on a selected group of students into their pro-environmental beliefs and behaviour. The research adopted the method of a diagnostic poll using an original survey. The aim of the article is to show the views concerning environmental protection held by students of management as well as their related behaviour in selected areas. The results indicate a discrepancy between students’ declarations and their environmental behaviour. Moreover, the results show that students’ beliefs and behaviour are consistent with country-wide trends related to beliefs and behaviour towards environmental conservation. The results stress the need to undertake informative and educational projects especially aimed at young adults who are entering the job market
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 191-201
Keywords: ecological awareness; pro-ecological attitudes; pro-ecological behavior; students; świadomość ekologiczna; postawy proekologiczne; zachowania proekologiczne; studenci